2013
DOI: 10.2169/internalmedicine.52.9076
|View full text |Cite
|
Sign up to set email alerts
|

A Liver Abscess Deprived a Healthy Adult of Eyesight: Endogenous Endophthalmitis Associated with a Pyogenic Liver Abscess Caused by Serotype K1 <i> Klebsiella Pneumonia</i>

Abstract: Klebsiella pneumonia usually causes urinary tract infections, pneumonia, and other infectious diseases in hospitalized and immunocompromised patients. Among the types of Klebsiella pneumonia, serotype K1 is known to be a highly virulent pathogen. We herein report the case of a healthy 63-year-old man with a pyogenic liver abscess and bilateral endogenous endophthalmitis caused by serotype K1 Klebsiella pneumonia. Although the patient received percutaneous abscess drainage and antibiotic therapy, he lost his ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
0
13
0
4
Order By: Relevance
“…Capsular serotype K1 has been generally considered to be the predominant virulent strain of K. pneumoniae capable of producing a capsular polysaccharide-presenting hypermucoviscosity, which is more resistant to phagocytosis [14,15,16]. A recent report has documented that serotype K1 K. pneumoniae is also capable of causing ocular or CNS complications from pyogenic liver abscess [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capsular serotype K1 has been generally considered to be the predominant virulent strain of K. pneumoniae capable of producing a capsular polysaccharide-presenting hypermucoviscosity, which is more resistant to phagocytosis [14,15,16]. A recent report has documented that serotype K1 K. pneumoniae is also capable of causing ocular or CNS complications from pyogenic liver abscess [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has documented that serotype K1 K. pneumoniae is also capable of causing ocular or CNS complications from pyogenic liver abscess [17]. Other factors associated with the invasive syndrome are hypermucoviscous phenotype, presence of virulence-associated genes such as rmpA and magA ; magA is a part of the gene cluster for serotype K1 capsular formation [14,15,16], and rmpA is a regulatory gene responsible for the hypermucoviscous phenotype [1]. Yu et al [18] had reported previously that the presence of the rmpA gene may contribute to expression of the hypermucoviscosity phenotype, in addition, the metastatic infection.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae'ye bağlı invazif karaciğer apsesi sendromu hakkında çalışmalar daha çok Doğu Asya ülkelerinden, özellikle Tayvan'dan bildirilmiştir (4,(6)(7)(8). Son yıllarda ABD, Avrupa ve Avustralya'dan da olgu bildirimleri yapılmıştır (9)(10)(11)(12)(13)(14).…”
Section: İrdelemeunclassified
“…K. pneumoniae suşlarının, belirli primerler kullanılarak polimeraz zincir reaksiyonu (PZR) ile wzx ve wzy lokuslarında K1 ve K2 serotiplerine özgü alellerin saptanmasıyla serotip tayininin yapıldığı bir çalışmada en sık bu iki serotipin neden olduğu saptanmıştır (5). Ek olarak serotip K1 endoftalmi komplikasyonuyla ilişkili bulunmuştur (5,8). Lin ve arkadaşları (18)'nın Hong Kong, Tayvan ve Singapur hastanelerinde yaptığı çok merkezli bir çalışmada, karaciğer apsesi olan ve sağlıklı taşıyıcılarda saptanan K. pneumoniae suşlarının virülansı incelenmiştir.…”
Section: İrdelemeunclassified
“…It is associated with underlying immunosuppressive conditions, including diabetes mellitus, HIV infection, indwelling catheters, cardiac disease, renal insufficiency, malignancy, or immunosuppressive therapy (1)(2)(3)(4)(5). Moreover, EBE is a rare but potential complication of neonatal sepsis (6).…”
mentioning
confidence: 99%